(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background : Atrial fibrillation(AF) is the most common sustained arrhythmia encountered in clinical practice,accounting 1/3 of hospital-admissions for arrhythmia and rate of admissions for AF has risen recently.The principle significance of AF both to patient and healthcare system is fivefold increased risk of embolic stroke. Methodology: Electrocardiogram confirmed 100 adult(≥18 years) patients of AF were included in this study and evaluated clinically. Results: Incidence of AF in India is significantly high in younger age group and in Female(58%) as compared to Western countries,where AF is more common in old age and in Male(42%).Most common cause of AF is Rheumatic heart disease as compared to Western countries,where IHD is the commonest cause.The average age of patient having RHD developing AF,in India,is 15-20 years earlier than patients from Western countries.Most common complication of AF is Congestive cardiac failure. Most serious complication of AF is Cardio-embolic stroke.Increase in size of Left Atrium in AF is associated with increased risk of Cardio-embolic stroke. Conclusion: Trials have shown reduction in risk,if patients are adequately anticoagulated.so early evaluation and prophylactic treatment can reduce mortality and morbidity in patients of AF